Dietary insulin load and index in relation to incident gestational diabetes mellitus: a prospective cohort study - Azadeh Aminianfar; Hamid Zolfaghari; Sanaz Soltani; Hossein Hajianfar; Leila Azadbakht; Zahra Shahshahan; Ahmad Esmaillzadeh (Scientific Reports)
Abstract No study has examined the association between dietary insulin load (DIL) and insulin index (DII) with developing gestational diabetes mellitus (GDM) during pregnancy. This study aimed to investigate the association between DIL and DII and risk of GDM in a group of pregnant women in Iran. In this prospective cohort study, 812 pregnant in their first trimester were recruited and followed. Usual dietary intakes were measured using a validated 117-item semi-quantitative food frequency questionnaire at weeks 8–16 of gestations. DIL and DII were calculated based on earlier publications. GDM was diagnosed based on the results of a 50 g, 1 h oral glucose tolerance test at 24–28 weeks of gestation. Cox proportional hazards model was used to compute relative risks ratios (RRs) and 95% confidence intervals (CI) for GDM. Mean ± SD of age and BMI of study participants was 29.4 ± 4.84 y and 25.14 ± 4.08 kg/m2, respectively at study baseline. Mean ± SD of DIL was 80,629 ± 29,328 and mean ± SD of DII was 40.23 ± 4.93. Overall, 28.4% (n = 231) of study population developed GDM at weeks 24–28 of pregnancy. After adjustment for potential confounding variables, we found that women in the highest quartile of DIL had 53% elevated risk of GDM (95% CI 1.003, 2.34; P-trend = 0.14) compared with those in the lowest quartile. Additional adjustment for weight gain during pregnancy did not alter the association (RR = 1.53; 95% CI 1.003, 2.34; P-trend = 0.14). Women with the greatest DII had a 23% non-significant elevated risk of GDM (95% CI 0.84, 1.82; P-trend = 0.55) compared to those with the lowest DII. We found that women with the highest DIL were at greater risk of developing GDM during pregnancy. No significant association was seen between DII and risk of GDM.